KOMBINASI TEORI VYGOTSKY DAN POLYA UNTUK MENINGKATKAN KEMAMPUAN PEMAHAMAN KONSEP MAHASISWA ERA 4.0 - Suendri Suendri; Riri Syafitri Lubis; Mohammad Badri (Universitas Negeri Medan, 2021)
Abstract:This study aims to determinehow the effect of a combination of Vygotsky and Polya's Problem Based Instruction (PBI) learning model to improve students' conceptual understanding in facing Era 4.0. This research was implemented at the State Islamic University of North Sumatra in Medan City with a population of all fourth-semester students by taking a sample through a random sampling technique. This study used a quasi-experimental method with a post-test control group design. To collect data, the instrument used was a test. Testing of the test instruments consists ofcontent validity, reliability, difficulty level, and distinguishing power. The prerequisite test includes the normality test and homogeneity test with a significant level of 5%. Hypothesis testing using the t-test in testing one average. It is hoped that the problem-solving process created by students actually meets the criteria for understanding the concept in the combination learning group of PBI learning models. The treatment will be carried out in one group with a different time and place, namely students of the Mathematics study program who are taking linear algebra lectures in the fourth semester. The research findings recommend that the combination of PBI learning models be used as one of the learning approaches used in primary schools to achieve competence and have high creativity for Era 4.0 students.Keywords: Learning Model, Problem Based Instruction, Vygotsky, PolyaAbstrak:Penelitian ini bertujuanuntuk mengetahui bagaimana pengaruh kombinasi model pembelajaran Problem Based Instruction (PBI) Vygotsky dan Polya untuk meningkatkan pemahaman konsep mahasiswa dalam menghadapi Era 4.0.Penelitian ini dilaksanakan di Universitas Islam Negeri Sumatera Utara yang ada di Kota Medan dengan populasi seluruh mahasiswa semester IV dengan mengambil sampel melalui teknik random sampling. Penelitian ini menggunakan metode eksperimen semu dengan rancangan penelitian post-test control group design. Untuk mengumpulkan data,instrumen yang digunakan adalah tes. Pengujian instrumen tes terdiri darikesahihanisi, reliabilitas, tingkat kesulitan, dan daya pembeda. Uji prasyarat meliputi uji normalitas dan uji homogenitas dengan taraf signifikan 5%. Uji hipotesis menggunakan uji t dalam pengujian satu rata-rata. Proses pemecahan masalah yang dilakukanoleh mahasiswadiharapkan dapat memenuhi kriteria pemahaman konsep padakelompok pembelajaran kombinasi model pembelajaaran PBI. Perlakuan akan dilakukan satu kelompokdengan waktu danlokasi yang berbeda, yaitu mahasiswa jurusan Matematika yang sedang mengikuti Mata KuliahAljabar Linier di semester IV. Temuan penelitian merekomendasikan kombinasi model pembelajaran PBI dapat digunakansebagai metode pembelajaran yang digunakandi sekolah utamanya untuk mencapai kompetensi dan memiliki kreativitas yang tinggi bagi mahasiswa Era 4.0.Kata kunci: Metode Pembelajaran, Problem Based Instruction, Vygotsky, Polya